Pengaruh Literasi Keuangan Syariah Terhadap Pengambilan Keputusan Finansial Generasi Z - Eva Mawarni Putri; Nadia Sari SW; Moniqa Astrid; Muhammad Arfan Harahap (Digital Bisnis: Jurnal Publikasi Ilmu Manajemen dan E-Commerce, 2025)
This study aims to analyze the influence of Islamic financial literacy on the financial decision-making of Generation Z, a demographic group that is currently the most active in digital economic activities. Islamic financial literacy is viewed as an essential competency that includes understanding fundamental principles such as the prohibition of riba, profit-sharing concepts, risk management, and social responsibility in financial transactions. In the context of rapid financial technology development and increased access to various Islamic financial products, the ability of Generation Z to comprehend and apply these principles becomes a determining factor in the quality of their financial decisions. This study also highlights that Generation Z tends to exhibit high levels of consumptive behavior, making adequate knowledge of Islamic finance crucial in shaping their financial planning patterns, investment preferences, and level of caution when selecting financial instruments. Furthermore, the study emphasizes that Islamic financial literacy influences not only practical financial management aspects but also ethical and value-based perspectives that shape the financial mindset of Generation Z. The findings are expected to contribute to the development of more effective and targeted Islamic financial education strategies.